MODERNIZATION OF HYDROPNIC FARMERS THROUGH THE APPLICATION OF INTERNET OF THINGS-BASED AUTOMATION SYSTEMS TO IMPROVE THE QUALITY OF CROP PRODUCTS - Prisma Megantoro; Muhammad Akbar Syahbani; Hafidz Faqih Aldi Kusuma; Sigit Dani Perkasa; Diaz Samsun Alif; Abdul Abror; Rizki Putra Prastio (Jurnal Layanan Masyarakat, 2023)
Hydroponics is one of the agricultural techniques with great potential to produce plant products. Hydroponics is also a pattern of plant breeding that is environmentally friendly and does not require a large area of ​​land. Although it has been developed for long time ago, the quality and quantity of hydroponics does not really give significant results. In order to improve the quality of agricultural products, a modernization step is needed by implementing an automation system based on Internet of Things. Thus, the solution offered to overcome the problems of the current hydroponic system, the innovation offered is green hardware, namely Airlangga Sahabat Petani Hidroponik (Arsenik). In this hardware, monitoring of the system with an integrated manner and measuring several aspects such as environmental and soil levels, nutrients in plants and interpreting them into an output that can be read directly by users. The expected result through this hardware is community empowerment in developing hydroponic systems and maximum hydroponic plant yields.